Impact of Tumor Histology on Resectability and Neurological Outcome in Primary Intramedullary Spinal Cord Tumors: A Single-Center Experience With 102 Patients. (March 2015) - Karikari, Isaac O.; Nimjee, Shahid M.; Hodges, Tiffany R.; Cutrell, Erin; Hughes, Betsy D.; Powers, Ciaran J.; Mehta, Ankit I.; Hardin, Carolyn; Bagley, Carlos A.; Isaacs, Robert E.; Haglund, Michael M.; Friedman, Allan H.
Abstract : BACKGROUND: Surgical outcomes for intramedullary spinal cord tumors are affected by many variables including tumor histology and preoperative neurological function. OBJECTIVE: To analyze the impact of tumor histology on neurological outcome in primary intramedullary spinal cord tumors. METHODS: A retrospective review of 102 consecutive patients with intramedullary spinal cord tumors treated at a single institution between January 1998 and March 2009. RESULTS: Ependymomas were the most common tumors with 55 (53.9%), followed by 21 astrocytomas (20.6%), 12 hemangioblastomas (11.8%), and 14 miscellaneous tumors (13.7%). Gross total resection was achieved in 50 ependymomas (90.9%), 3 astrocytomas (14.3%), 11 hemangioblastomas (91.7%), and 12 miscellaneous tumors (85.7%). At a mean follow-up of 41.8 months (range, 1-132 months), we observed recurrences in 4 ependymoma cases (7.3%), 10 astrocytoma cases (47.6%), 1 miscellaneous tumor case (7.1%), and no recurrence in hemangioblastoma cases. When analyzed by tumor location, there was no difference in neurological outcomes ( P = .66). At the time of their last follow-up visit, 11 patients (20%) with an ependymoma improved, 38 (69%) remained the same, and 6 (10.9%) worsened. In patients with an astrocytoma, 1 (4.8%) improved, 10 (47.6%) remained the same, and 10 (47.6%) worsened. One patient (8.3%) with a hemangioblastoma improved and 11 (91.7%) remained the same. No patient with a hemangioblastoma worsened. In the miscellaneous tumor group, 2 (14.3%) improved, 10 (71.4%) remained the same, and 2 (14.3%) worsened. Preoperative neurological status ( P = .02), tumor histology ( P = .005), and extent of resection ( P < .0001) were all predictive of functional neurological outcomes. CONCLUSION: Tumor histology is the most important predictor of neurological outcome after surgical resection because it predicts resectability and recurrence. ABBREVIATIONS: GTR, gross total resection;IMSCT, intramedullary spinal cord tumor;MMS, Modified McCormick Scale;POD, plant of dissection;STR, subtotal resection